MANAJEMEN KEPALA SMA NEGERI 4 SINGKAWANG DALAM MENINGKATKAN MOTIVASI GURU BERPRESTASI - Nunuk Mintarsih; Usman Radiana; M. Syukri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to determine the management of the Principal of SMA Negeri 4 Singkawang in increasing teacher motivation to excel. This form of research uses a qualitative approach. Research participants amounted to 4 people. Data collection techniques with interviews, documentation, and observation. Data analysis uses data reduction, data display and verifications. The technique of checking the validity of the data is through triangulation and member check. The main findings indicate that: 1) planning is carried out through the formulation of the vision and mission, making planning programs, and involving the entire school community, 2) organizing is carried out through the formation of the School Development Team, division of tasks, preparation of organizational structure, 3) implementation is carried out through program preparation. work, mapping of teacher abilities, and utilization of information systems, 4) supervision is carried out on a scheduled basis in the form of supervision, and 5) Evaluation is carried out to overcome existing obstacles. The conclusion of this research is that the principal's management has been implemented well in order to increase the motivation of teachers to excel. The implications of this research can be used as input in increasing teacher motivation for achievement through the application of management functions.